Investment Support for Innovation Activity of Enterprises in Ukraine - Juryniec, Zoryna (Journal of Finance and Financial Law, 2014)
This article analyzes the influence of the factors on investment and innovation activity of enterprises in Ukraine. The paper presents the study of innovation activity of industrial enterprises. The author substantiates financing of innovation activity sources of enterprises. This will contribute to the expansion of possibilities for innovation development. The article deals with problems which arise in the field of investments in innovation sphere and in the defining of cost structure by financing sources of innovative activity. The research provides the ways of solving problems in modern conditions of economy development and visions of formation, planning and implementation of the strategic directions of innovative development of enterprises.